Mass-kill hunting and Late Quaternary ecology: New insights into the 'desert kite' phenomenon in Arabia. (June 2021) - Groucutt, Huw S.; Carleton, W. Christopher
Highlights: Desert kites are stone structures typically interpreted as mass-kill hunting traps. Here we explore the spatial distribution of desert kites. We found hundreds of new desert kites, particularly around Harrat Nawasif. Relative chronology indicates a prolonged history of kite construction in Arabia. Abstract: Over 6, 000 'desert kites'—mass-kill stone hunting traps constructed at various times over the last 10, 000 years—have been identified from northern Arabia to western central Asia. It has been proposed that kites had a significant impact on animal demography, leading to changes in ecology and human societies. While there has been considerable discussion regarding the function and chronology of kites, their spatial distribution is poorly understood. Here we report over 300 desert kites from several areas of the Arabian Peninsula, including ~ 500 km further south than previously suggested. Using satellite imagery, we studied their super-imposition revealing an extended chronology of kite-construction, including multiple phases of rebuilding in some cases and kites built relatively recently. This shows that desert kites were significantly more spatially and temporally widespread than previously believed, suggesting that they played a role in transforming Late Quaternary ecosystems and offering insights into the behaviour of human societies in challenging environments.